Challenges Faced by South African Law Enforcement Agencies in Policing the Illicit Population in South Africa - Malatji, Thabiso; Rakubu, Kholofelo; Ragolane, M. (Universitas Medan Area, 2024)
In the last decade, South Africa has experienced an influx of undocumented immigrants. This causes strain on government departments in dealing with the number of people entering the country illegally. It further creates a problem within the legal policy frameworks on managing immigration. Ongoing deliberations regarding undocumented immigrants have continued to spread across the country, which raises a more complex phenomenon of causing panic among the public and political officials and needing thorough attention from policymakers. This study aimed to investigate the challenges faced by South African law enforcement agencies in dealing with the illicit population. Although policing of illegal immigrants has developed in a vacuum, there is a need for a more sensitive approach to the attributes that lead to the escalation of illicit immigrants. The findings reveal that the management of illegal immigrants has become a problem for which departments show little care or concern due to a lack of collaborative efforts and policy implementation. There is also a lack of cooperation, crime is rising, cities and communities are overcrowded, and the public has turned to their methods of resolving the problem. The methodology adopted in this study was qualitative, and data were collected using secondary sources and materials. This paper aimed to assess the role of law enforcement agencies in dealing with the illicit population.